Anchoring K+ in Li+ Sites of LiNi0.8Co0.15Al0.05O2 Cathode Material to Suppress its Structural Degradation During High‐Voltage Cycling. Issue 12 (24th October 2018) - Zhao, Junkai; Wang, Zhixing; Wang, Jiexi; Guo, Huajun; Li, Xinhai; Gui, Weihua; Chen, Ning; Yan, Guochun
Abstract: The rapid rise of electrode impedance and capacity decay of Ni‐rich layered cathode materials during high‐voltage cycling are rooted in their severe structural degradation. Here we present a feasible strategy, anchoring ∼1 % K + into the Li + sites of LiNi0.8 Co0.15 Al0.05 O2 as an excellent structural stabilizer, to overcome aforementioned issues, and the similarities and differences in terms of modification mechanism is compared with Na + . Showing difference with Na + that tends to migrate into electrolyte during high‐voltage cycling, K + occupies in Li + site firmly because of its larger ionic radius and lower migrating ability, which sustainably prevent the irreversible phase transition between two hexagonal phases (H2 and H3) and impede the cation migration in highly delithiated state, thus suppressing the structural degradation. Benefiting from these merits, Li0.99 K0.01 Ni0.8 Co0.15 Al0.05 O2 delivers a large initial discharge capacity of 217 mAh g −1 at 0.1 C and maintains stable cycling at 1 C in a high voltage of 4.6 V (remaining 87.4 % of its initial capacity after 150 cycles). The mechanism proposed in this work, accounting for enhanced structural stability under high‐voltage cycling by K + anchoring in Ni‐rich cathode materials, provides a vital hint for rational designing advanced cathode materials to pursue high energy density Li‐ion batteries. Abstract : K + anchoring in Li + sites of LiNi0.8 Co0.15 Al0.05 O2 prevent the collapse of host structure and inhibit cation migration in highly delithiated state. Benefit from these, Li0.99 K0.01 Ni0.8 Co0.15 Al0.05 O2 exhibits superior high‐voltage electrochemical performances.